(untitled) (Scientific journal of the Fergana State University, 2025)
The article explores the theoretical and methodological foundations for developing ideological and ideological competence in future educators, the practical methodological system for developing this competence, and the effectiveness of developing ideological and ideological competence in future educators. Additionally, the methods for developing ideological and ideological competence in future educators are analyzed.